Alphavirus-derived small RNAs modulate pathogenesis in disease vector mosquitoes - Myles, Kevin M; Wiley, Michael R; Morazzani, Elaine M; Adelman, Zach N (Proceedings of the National Academy of Sciences - PNAS, 2008)
Mosquito-borne viruses cause significant levels of morbidity and mortality in humans and domesticated animals. Maintenance of mosquito-borne viruses in nature requires a biological transmission cycle that involves alternating virus replication in a susceptible vertebrate and mosquito host. Although the vertebrate infection is acute and often associated with disease, continual transmission of these viruses in nature depends on the establishment of a persistent, nonpathogenic infection in the mosquito vector. An antiviral RNAi response has been shown to limit the replication of RNA viruses in flies. However, the importance of the RNAi pathway as an antiviral defense in mammals is unclear. Differences in the immune responses of mammals and mosquitoes may explain why these viruses are not generally associated with pathology in the invertebrate host. We identified virus-derived small interfering RNAs (viRNAs), 21 nt in length, in Aedes aegypti infected with the mosquito-borne virus, Sindbis (SINV). viRNAs had an asymmetric distribution that spanned the length of the SINV genome. To determine the role of viRNAs in controlling pathogenic potential, mosquitoes were infected with recombinant alphaviruses expressing suppressors of RNA silencing. Decreased survival was observed in mosquitoes in which the accumulation of viRNAs was suppressed. These results suggest that an exogenous siRNA pathway is essential to the survival of mosquitoes infected with alphaviruses and, thus, the maintenance of these viruses in nature.